Low Levels of Neutralizing Antibodies After Natural Infection With Severe Acute Respiratory Syndrome Coronavirus 2 in a Community-Based Serological Study. (2nd March 2022) - McDade, Thomas W; Sancilio, Amelia; D'Aquila, Richard; Mustanski, Brian; Vaught, Lauren A; Reiser, Nina L; Velez, Matthew E; Hsieh, Ryan R; Ryan, Daniel T; Saber, Rana; McNally, Elizabeth M; Demonbreun, Alexis R
Abstract: Background: Confidence in natural immunity after infection with severe acute respiratory syndrome coronavirus 2 is one reason for vaccine hesitancy. Methods: We measured antibody-mediated neutralization of spike protein-ACE2 receptor binding in a large community-based sample of seropositive individuals who differed in severity of infection (N = 790). Results: A total of 39.8% of infections were asymptomatic, 46.5% were symptomatic with no clinical care, 13.8% were symptomatic with clinical care, and 3.7% required hospitalization. Moderate/high neutralizing activity was present after 41.3% of clinically managed infections, in comparison with 7.9% of symptomatic and 1.9% of asymptomatic infections. Conclusions: Prior coronavirus disease 2019 infection does not guarantee a high level of antibody-mediated protection against reinfection in the general population. Abstract : Prior exposure to severe acute respiratory syndrome coronavirus 2 results in low levels of antibody-mediated protection against reinfection in a large, community-based sample where the majority of infections did not require clinical care or hospitalization.